Effect of freeze-thaw pretreatment on yield and quality of perilla seed oil. (March 2020) - Lee, Kyo-Yeon; Rahman, M. Shafiur; Kim, Ah-Na; Son, Yejin; Gu, Suyeon; Lee, Myoung-Hee; Kim, Jung In; Ha, Tae Joung; Kwak, Doyeon; Kim, Hyun-Jin; Kerr, William L.; Choi, Sung-Gil
Abstract: This work investigated the effect of freeze-thaw (FT) pretreatment on the yield and quality of oil cold-pressed from perilla seeds. FT pretreatment ruptured the perilla seed coat and internal structure, resulting in an oil yield of 78.71%, about 2.5-times greater than the yield from untreated control perilla seeds. Acid values were relatively low (0.54 mg KOH/g) and not different in the FT-treated and control oil. Likewise, peroxide values were low (1.34 meq/kg) and not different amongst the treatment groups. Viscosity values (96.5 mPa s) were indicative of a light oil while color values (L*a*b*) indicated a light yellow-green color. The major unsaturated fatty acids were identified as linolenic acid (C18:3, ω−3), linoleic acid (C18:2, ω−6), and oleic acid (C18:1, ω−9). The most abundant volatiles were 1-(furan-2-yl)-4-methylpentan-1-one and 3-(4-methyl-3-pentenyl)-furan in both of the oil samples. However, the normalized relative intensity of the volatile compounds was reduced in the FT-treated PO. The acylglycerol profile in FT-treated and control PO was not different, yet another indication that FT pretreatment did not increase oil rancidity or oxidative instability. FT pretreatment on oil seeds before cold-pressing is an attractive technique for obtaining high oil yield without deteriorative effects on the quality characteristics of edible oil. Highlights: Freeze-thaw (FT) pretreatment on perilla seeds led to ruptured cellular structure. FT treatment resulted in about 2.5-times higher oil yield (78.71%) than control sample. Physicochemical properties and fatty acid profile in oil was not affected by FT treatment. The volatile compounds were slightly reduced in FT-treated perilla oil. Glyceride profiles in FT-treated oil were not changed by FT pretreatment.